Potential of Hibiscus (Hibiscus rosa-sinensis L.) Extract as a Substitute for Eosin in Hematoxylin-Eosin Histological Staining - Nadifah, Fitri; Prasetyaningsih, Yuliana; Muhajir, Nurlaili Farida; Murtiningrum, Sri; Ohoiwutun, Clara Shinta D.P; Puspita, Elisabet Della (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Staining is an important stage in preparing microscopic preparations so that the histological structure can be observed clearly. Hematoxylin-Eosin is the most widely used dye. Unfortunately, eosin is a synthetic chemical compound that is carcinogenic. To reduce the health and environmental impacts of eosin compounds, it is important to look for alternative dyes from natural ingredients. Hibiscus (Hibiscus rosa-sinensis L.) is a plant known to contain anthocyanins which can be used as eosin substitutes. This study aims to determine the potential of hibiscus extract as a substitute for eosin in histological staining. In this study, unstained liver tissue preparations from mice (Mus musculus) were used. Hibiscus extract dye was compared with eosin as a control. The color quality of the tissue preparations was used as an experimental parameter. The results of the microscopic assessment showed that liver tissue stained with Hibiscus extract at concentrations of 60% and 80% was less good than eosin. However, because tissue can stain reddish, hibiscus extract has the potential to be used as an eosin substitute. The right extraction method may be able to produce intact anthocyanin so that it can color the tissue optimally.